2016
DOI: 10.1088/0957-4484/27/23/235702
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bending stiffness on scaling laws for the size of colloidal nanosheets

Abstract: Using coarse-grained Brownian dynamics simulations, we study the relationship between hydrodynamic radius ([Formula: see text] and the lateral size ([Formula: see text] of dispersed nanosheets. Our simulation results show that the bending modulus of the nanosheets has a significant impact on the exponent of this power-law relationship between the radius of gyration (and thus [Formula: see text] and [Formula: see text] The exponent can vary from 0.17 to 1. This sheds light on the interpretation of dynamic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23] By supplementing self-avoidance (materials do not penetrate themselves) 15 and surface interactions, rich conformations were predicted in the framework of Landau-Ginsburg theory of phase transitions, including flat, crumpled, folded, compact, anisotropic tubular, and globular phases. [24][25][26][27] Specifically, some simulation results revealed that the variation in bending stiffness 28,29 and surface adhesion 30 of 2D macromolecules does modify the conformation. Rich emergent behaviors of 2D macromolecules can be triggered, provided with the wide range of elastic responses as tuned by functionalization and defect engineering, [31][32][33] as well as the complexity in intermolecular and intramolecular interactions (e.g., attraction from van der Waals interaction, 34 hydrogen bonding, 35 opposite-charge Coulomb interaction and repulsion from like-charge Coulomb interaction, 36 Pauli repulsion 37 ).…”
Section: Progress and Potentialmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] By supplementing self-avoidance (materials do not penetrate themselves) 15 and surface interactions, rich conformations were predicted in the framework of Landau-Ginsburg theory of phase transitions, including flat, crumpled, folded, compact, anisotropic tubular, and globular phases. [24][25][26][27] Specifically, some simulation results revealed that the variation in bending stiffness 28,29 and surface adhesion 30 of 2D macromolecules does modify the conformation. Rich emergent behaviors of 2D macromolecules can be triggered, provided with the wide range of elastic responses as tuned by functionalization and defect engineering, [31][32][33] as well as the complexity in intermolecular and intramolecular interactions (e.g., attraction from van der Waals interaction, 34 hydrogen bonding, 35 opposite-charge Coulomb interaction and repulsion from like-charge Coulomb interaction, 36 Pauli repulsion 37 ).…”
Section: Progress and Potentialmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 , 8 Numerical simulations using the self-penetrable phantom model of tethered membranes confirm the stability of quasi-flat conformation and revealed the crumpling transition at high temperature. 9 , 10 , 11 Considering the effects of self-avoiding, bending resistance, and surface interaction, simulations of more realistic models predict flat, rippled, wrinkled, crumpled, folded, scrolled, and compact phases, 6 , 12 , 13 , 14 , 15 , 16 , 17 , 18 which are validated by the experimental studies 19 , 20 , 21 , 22 , 23 ( Figure 1 A).
Figure 1 Morphological phases of 2D macromolecules (A) Phases identified from theoretical and experimental studies, which include the flat, 6 , 13 , 14 quasi-flat, 9 , 18 rippled, 19 wrinkled, 20 folded, 13 , 15 , 16 , 23 scroll, 21 , 22 crumpled, 10 , 12 , 14 , 17 , 18 and compact 13 , 14 phases.
…”
Section: Introductionmentioning
confidence: 53%
“… (A) Phases identified from theoretical and experimental studies, which include the flat, 6 , 13 , 14 quasi-flat, 9 , 18 rippled, 19 wrinkled, 20 folded, 13 , 15 , 16 , 23 scroll, 21 , 22 crumpled, 10 , 12 , 14 , 17 , 18 and compact 13 , 14 phases. Similar morphological complexity can be found in the red blood cells (RBCs) 24 and the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a large amount of uncertainty in the lateral size measurement, DLS has been found to be useful for comparing significant differences in nanosheet size. [ 27 ] The mean hydrodynamic diameter ( d hd ) attained from DLS can be approximated as the diameter of a sphere with volume equal to the mean GO/rGO sheet volume. The d hd was measured before and after the processing of GO to rGO, Figure a, and a roughly 40% shift in the average particle's d hd was observed with the d hd of both GO and rGO found to be 478 ± 9 to 285 ± 3 nm, respectively.…”
Section: Figurementioning
confidence: 99%